An efficient clock offset datum switching compensation method for BDS real-time satellite clock offset estimation. Issue 4 (15th August 2021) - Xie, Wei; Huang, Guanwen; Fu, Wenju; Li, Pingli; Cui, Bobin
Abstract: The quality of real-time satellite clock offsets products is one of the key elements for real-time satellite clock performance monitoring and real-time precise point positioning (PPP). However, impacted by the station location, environment, communication equipment, receiver performance, network delay, temporary modem failure or other reasons, the observation data of clock offset datum receiver occasionally outage, resulting in all satellite clocks offset cannot be estimated. In this contribution, an efficient clock offset datum switching compensation method for BDS real-time satellite clock offset estimation is proposed. One hundred stations distributed around the world, from day of year (DOY) 074 to 075 in 2019 are used to estimate BDS real-time satellite clock offset. Four schemes: clock offset datum switching without compensation (S1), clock offset datum switching with satellite clock offset jump compensation (S2), clock offset datum switching with satellite clock offset jump and receiver clock drift compensation (S3, the proposed method), clock offset datum without switching (S4), are used to validate the proposed method. By using the proposed method, the satellite clock offset jump can be eliminated and the satellite clock offset consistency can be maintained. The satellite clock offsets STD for S1, S2, S3 and S4 are 0.184, 0.183, 0.183 and 0.150 ns, respectively. The fitting precision of S1, S2, S3 and S4 are 70907.344, 0.731, 0.502 and 0.543 ns, respectively. The frequency stability of S3 shows the best performance among S2, S3 and S4 when the averaging interval time is 10, 000 and 20, 000 s, which can be attributed to the effectiveness of proposed method and frequency stability difference of clock offset datum receiver. The fitting precision and frequency stability cannot be reflected correctly by clock offset due to the satellite clock offset jump in S1. For precise point positioning (PPP), the coordinates jump and re-convergence can be eliminated by using the proposed method. Thus, this method can provide a reference for obtaining real-time, continuous and reliable BDS satellite clock offset products.